Pengelompokkan Kabupaten/Kota di Provinsi Sumatera Barat Berdasarkan Indikator Kesejahteraan Rakyat Menggunakan Algoritma SOM - Winartha, Mardia; Wirdiastuti, Chairina; Salma, Admi (Jurnal Riset Statistika, 2025)
Abstract. People's welfare is the main indicator in measuring the success of a region's development. Welfare reflects the fulfillment of people's basic needs, both material and spiritual, as measured through indicators of people's welfare. West Sumatra Province still shows a welfare gap between districts/municipalities, which can be seen from significant differences in indicators such as employment and poverty. Therefore, the purpose of this article is to cluster districts/cities in West Sumatra Province and recognize the characteristics of each cluster according to the people's welfare indicators in 2023 using the self-organizing maps algorithm. The results of the analysis show that 3 clusters are the optimal number of clusters. Cluster 1 includes 7 districts/cities with higher welfare levels, cluster 2 includes 7 districts/cities with medium welfare levels, and cluster 3 includes 5 districts/cities with lower welfare levels. This article is expected to help create better and more equitable policies that will support the improvement of people's welfare in West Sumatra Province. Abstrak. Kesejahteraan rakyat menjadi indikator utama dalam mengukur keberhasilan pembangunan suatu wilayah. Kesejahteraan mencerminkan kondisi terpenuhinya kebutuhan dasar masyarakat, baik material maupun spiritual yang diukur melalui indikator-indikator kesejahteraan rakyat. Provinsi Sumatera Barat masih menunjukkan kesenjangan kesejahteraan antar kabupaten/kota yang terlihat dari perbedaan signifikan pada indikator seperti ketenagakerjaan dan kemiskinan. Oleh sebab itu, tujuan dari artikel ini adalah untuk mengelompokkan kabupaten/kota di Provinsi Sumatera Barat dan mengenali karakteristik setiap cluster sesuai dengan indikator kesejahteraan rakyat pada tahun 2023 menggunakan algoritma self-organizing maps. Hasil analisis menunjukkan bahwa 3 cluster adalah jumlah cluster optimal. Cluster 1 meliputi 7 kabupaten/kota dengan tingkat kesejahteraan yang lebih tinggi, cluster 2 meliputi 7 kabupaten/kota dengan  tingkat kesejahteraan menengah, dan cluster 3 meliputi 5 kabupaten/kota dengan tingkat kesejahteraan yang lebih rendah. Artikel ini diharapkan dapat membantu menciptakan kebijakan yang lebih baik dan merata yang akan mendukung peningkatan  kesejahteraan rakyat di Provinsi Sumatera Barat.